2006
DOI: 10.1089/aid.2006.22.1172
|View full text |Cite
|
Sign up to set email alerts
|

HIV Type 1 Subtypes among STI Patients in Nairobi: A Genotypic Study Based on PartialpolGene Sequencing

Abstract: Circulating strains of human immunodeficiency virus (HIV) exhibit an extraordinary degree of genetic diversity and have been classified on the basis of relationships into distinct lineages called groups, types, subtypes, and subsubtypes. Sexually transmitted infections (STIs) are known to be a risk factor for HIV infection. To establish HIV-1 subtype diversity among STI patients in Nairobi, 140 samples were collected and partial pol gene sequencing done. From the analysis it was established that subtype A1 was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 14 publications
2
26
3
Order By: Relevance
“…[12][13][14] Little is known about circulating subtypes of HIV-1 in rural areas, which are the home to many of the infected people. In this study, we sought to determine the circulating subtypes of HIV-1 in eight districts of central Kenya in which HIV-1 prevalence has been known to be high.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14] Little is known about circulating subtypes of HIV-1 in rural areas, which are the home to many of the infected people. In this study, we sought to determine the circulating subtypes of HIV-1 in eight districts of central Kenya in which HIV-1 prevalence has been known to be high.…”
mentioning
confidence: 99%
“…Peripheral blood mononuclear cells (PBMCs) were extracted from whole blood by density gradient centrifugation using Ficoll-Paque Plus (Pharmacia) and Proviral DNA extracted using DNAzol (Gibco BRL) and ethanol precipitation as previously described. 12,13 A segment of the env gp41 (corresponding to nucleotide 7850-8310 of HIV-1 HXB2 ) was amplified with primers, gp40F1 5'-TCTTAGGAGCAGCAGGAAGCACTATGGG-3¢ and gp41R1 5'-AACGACAAAGGTGAGTATCCCTGCCTAA-3' in the first round and gp46F2 5'-ACAATTATTGTCTGGTA TAGTGCAACAGCA-3' and gp47R2 5'-TTAAACCTAT CAAGCCTCCTACTATCATTA-3' for nesting. Amplification was done with one cycle of 95°C for 10 min and 35 cycles of 95°C for 30 s, 55°C for 30 s, and 72°C for 1 min, with a final extension of 72°C for 10 min.…”
mentioning
confidence: 99%
“…In this study, 140 samples were collected and partial pol gene sequencing done. From the analysis it was established that subtype A1 was the major subtype (64%) followed by D (17%), C (9%), G (1%), and recombinants AD (4%), AC (3%), CRF02_AG (1%), and CRF16_A2D (1%) 24 . From April 2005 to July 2006 we carried a study in North Rift to determine the subtypes circulating based on the pol region (RT).…”
Section: Hiv-1 Diversity In Kenyamentioning
confidence: 99%
“…8 A study done in Kisumu, in western Kenya, looked at both env gp41 and a gag-pol segment for 460 individuals. It was found that 75% of the sequences had the same clade in both genomic regions; 59% of all sequences were clade A1 in both regions, 10% clade D, 3% clade C, and 2% clade G. 9 A study in a motherto-child transmission cohort located in the same area as the cohort described in this study used restriction fragmentlength polymorphism (RFLP) analysis of protease and p24 to determine clade and found that the majority of the 130 mothers were infected with clade A (58%), while 20% were clade D and 2% were clade C. 10 The most recent study published from Kenya examined integrase from 140 HIV-positive sexually transmitted infection patients in Nairobi, and found 64% of sequences were clade A1, 17% clade D, 9% clade C, and 1% clade G. 11 The only previous study from Kenya that used full-length sequence data examined 41 HIV-1 sequences collected from patients across southern Kenya. 12 It was reported that 56% of the sequences were nonrecombinant clade A, but only a single nonrecombinant clade C and a single nonrecombinant clade D sequence were found.…”
Section: Introductionmentioning
confidence: 99%
“…Those that examined a single HIV genomic region either did not identify recombination, 6 or found low levels, 8,10,11 to a maximum of 17% recombinant. 7 The study that examined two genomic regions identified a higher proportion of recombinants, of 25%.…”
Section: Introductionmentioning
confidence: 99%